California Supreme Court Justice Wiley Manuel Visits Office of Fresno County Counsel - Watkins, Howard::::::::: (1979)
Justice Wiley Manuel, Libby , David St. Louis, Baxter Richardson leaving Hilton Hotel ballroom Office law library in Hall of Records building 3rd floor